Spontaneous Platelet Aggregation in Arterial Insufficiency: Mechanisms and Implications - Wu, Kenneth K.; Hoak, John C. (Thrombosis and Haemostasis, 1976)
To investigate the clinical implications and mechanisms of spontaneous platelet aggregation (SPA) in man, 150 normal subjects, 22 patient controls and 130 patients with vascular insufficiency were studied. SPA was negative in normal subjects and patient controls whereas it was positive in 36 of 66 (54%) patients with transient ischemic attacks, 6 of 32 (19%) patients with stable angina, 7 of 10 (70%) patients with acute myocardial infarction and 11 of 14 (80%) patients with acute peripheral arterial insufficiency. The SPA was inhibited with aspirin in vivo, and inhibited competitively in vitro by low concentrations of aspirin, 2-chloroadenosine, prostaglandin E1 or apyrase but only by high concentrations of heparin or hirudin. Addition of platelet-poor plasma from patients with positive SPA did not cause normal platelets to aggregate. Treatment of patients who had acute peripheral arterial insufficiency with aspirin and dipyridamole prevented SPA with notable clinical improvement of the ischemic changes.